Uji Kandungan Bakteriologi Air Minum Isi Ulang di Wilayah Kerja Puskesmas Siko Kota Ternate - washliyah, Sitti; Sangadjisowohy, Idayani (Poltekkes Kemenkes Padang, 2023)
The rise of the Refill Drinking Water business is inseparable from the increasingly expensive of Ternate have water samples containing E coli bacteria. This can be caused by water price of Bottled Drinking Water. The aim of this research is to identify the E coli content in drinking water depots in the city of Ternate. This research used a descriptive research design using observational methods and laboratory tests and was carried out in the chemistry laboratory and workshop of the Environmental Health Department, Health Polytechnic, Ministry of Health, Ternate. The sample in this study was drinking water refills at 23 depots, by taking 300 cc of water samples. The results of the research showed that of the 23 drinking water depots examined, 7 samples contained E Coli bacteria. Of these, two are in Dufa-Dufa, two more depots are in Akehuda and the rest are located in Salero, Kasturian and SOA. The conclusion is that as many as 41% of all drinking water depots in the city reservoirs that are rarely cleaned, which can give rise to mold which can trigger the growth of bacteria, one of which is E coli. It is recommended that a thorough inspection of drinking water depots in Ternate City be carried out both by subsequent researchers and city officials.